Knowledge management strategies as a competitive advantage for delivering professional e-government services - Sabaghpour Azarian, Mahdieh; , Azarian; Nasiruzzaman, Md.; Huq, Md. Najibul; Ibrahim, Jamaludin (International Foundation for Research and Development (IFDR), 2013)
Nowadays, organizations emphasize on practicing knowledge management to achieve higher level of efficiencies across delivering professional services, improving accountability, making informed decisions, enhancing partnerships, capturing the knowledge of an ageing workforce and improving overall performance. This paper investigates on a number of new generation Knowledge Management strategies to improve professional e-government service deliveries, which drives competitive advantage of successful horizontal and vertical interaction. Moreover, transformation of e-government to m-government (m-government platform) and social media analysis, knowledge sharing and personalization are four main KM strategies those specifically are targeted to attract youth generation to effectively use online governmental services, thus a proposed framework through this paper illustrates how successful integration of KM strategies and professional e-government services drive competitive advantage.